Post-harvest chitosan treatment suppresses oxidative stress by regulating reactive oxygen species metabolism in wounded apples - Ackah, Sabina; Bi, Yang; Xue, Sulin; Yakubu, Salimata; Han, Ye; Zong, Yuanyuan; Atuna, Richard Atinpoore; Prusky, Dov (Frontiers in Plant Science, 2022)
Mechanical wound on fruit triggers the formation of reactive oxygen species (ROS) that weaken cell walls, resulting in post-harvest losses. This mechanism can be controlled by using fruit preservatives to stimulate fruit antioxidant enzyme activities for the detoxification of ROS. Chitosan is a safe and environmentally friendly preservative that modulates ROS in whole fruits and plant cells, but the effects of chitosan on the ROS metabolism of mechanically wounded apples during storage are unknown. Our study focused on exploring the effects of post-harvest chitosan treatment on ROS production, cell membrane integrity, and enzymatic and non-enzymatic antioxidant systems at fruit wounds during storage. Apple fruits (cv. Fuji) were artificially wounded, treated with 2.5% (w/v) chitosan, and stored at room temperature (21–25°C, RH = 81–85%) for 7 days. Non-wounded apples were used as healthy controls. The results showed that chitosan treatment stimulated the activities of NADPH oxidase and superoxide dismutase and increased the formation of superoxide anions and hydrogen peroxide in fruit wounds. However, malondialdehyde, lipoxygenase, and membrane permeability, which are direct biomarkers to evaluate lipid peroxidation and membrane integrity, were significantly decreased in the wounded fruits after chitosan treatment compared to the wounded control fruits. Antioxidant enzymes, such as peroxidase and catalase activities, were induced by chitosan at fruit wounds. In addition, ascorbate-glutathione cycle-related enzymes; ascorbate peroxide, monodehydroascorbate reductase, dehydroascorbate reductase, and glutathione reductase and the content of substrates, mainly ascorbic acid, dehydroascorbate, reduced glutathione, and glutathione, were increased at fruit wounds by chitosan compared to the wounded control fruits. Our results show that wounding stimulated the production of ROS or oxidative stress. However, treatment with chitosan triggered antioxidant systems to scavenge ROS and prevent loss of fruit membrane integrity. Therefore, chitosan promises to be a favorable preservative in inducing tolerance to stress and maintaining fruit quality.